Hubungan Kepatuhan Konsumsi Tablet FE dengan Kejadian Anemia pada Ibu Hamil Trimester III di RS Bhayangkara Banjarmasin - Kamrori Kamrori; Anik Purwati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
One of the government's steps to reduce maternal and infant mortality rates starts from adolescence by giving blood-boosting tablets to pregnant women Anemia is defined as a low hemoglobin (Hb) concentration in the blood. The high coverage of giving 90 Fe tablets to pregnant women does not guarantee a reduction in anemia if adherence to Fe tablets is still low. The research aims to determine the relationship between the level of compliance with the consumption of Fe tablets and the incidence of anemia in third trimester pregnant women. The observational research design uses a cross-sectional design. The research sample of third trimester pregnant women at Bhayangkara Banjarmasin Hospital consisted of 25 respondent. Sampling used Random Sampling technique. Data analysis includes univariate analysis and bivariate analysis using the Chi-Square statistical test. The statistical test results showed that there was a relationship between the level of compliance with the consumption of Fe tablets and the incidence of anemia in pregnant women in the third trimester at Bhayangkara Hospital, Banjarmasin. The lower the mother's level of compliance with taking Fe tablets, the greater the risk of developing anemia. The results of this study were that the majority of respondents studied had non-compliance in consuming blood supplement tablets (28%) and respondents who experienced anemia were (72%). The result was a p value <0.01, so there was a relationship between adherence to iron consumption and anemia. Respondents who did not comply with iron consumption had a 25.0 times greater risk of anemia. The conclusion in this study is that there is a relationship between compliance with Fe tablet consumption in TM III pregnant women and the incidence of anemia at Bhayangkara Banjarmasin Hospital.